Prohibition of discrimination on the grounds of national, ethnic, racial and religious affiliation in Polish law: real illusory protection - Haczkowska, Monika (Vergentis, 2025)
The principle of non-discrimination is guaranteed at the constitutional level in Polish law. Additionally, it results from international conventions to which Poland is a party as well as from EU law. Analyzing the legal provisions relating to the concept of prohibited discrimination on the grounds of, among others, sex, gender identity, skin color, language, national and/or ethnic origin, religion, denomination or lack of denomination, worldview, health condition and degree of ability, age, psychosexual orientation, social and economic status and others - one may get the impression that there are sufficient guarantees prohibiting worse or unequal treatment of persons. However, the practice differs from constitutional and international standards. The problem of discrimination affects many people or groups of people in various situations. The subject of this analysis will be legal protection against discrimination based on various aspects, including in labor law. The aim of this publication is to answer the question of whether the guarantees contained in the constitution and ordinary laws are sufficient to protect individual rights.